Becoming a more mindful practitioner: the effectiveness of a Mindfulness-based CBT course in meeting training needs for clinical staff in adult mental health Urgent Care services. (8th February 2016) - Moorhead, Cate; Winfield, Jill; Freeston, Mark H.
Abstract: This paper describes a service development which arose from an adult mental health inpatient ward team who wanted to be able to work more effectively to help patients who had major difficulties with emotion regulation. It was proposed that enhancing mindfulness through a Mindfulness-based Cognitive Therapy (MBCT) programme within the core staff team would enhance therapeutic milieu and therefore general outcomes associated with engagement and recovery. The training delivered was an adapted 8-week MBCT programme. A double baseline design was used with measures taken at 1 month before training and immediately before the programme started. Standardized and non-standardized measures were administered at pre-, mid-, post-, and 1-month follow-up points. Workshops and interviews supported the investigation of staff experience and impact of MBCT training. Participants in the training were nursing and occupational therapy staff. The trainer was the first author (C.M.), who is a cognitive behavioural therapist and mindfulness teacher at Newcastle Cognitive and Behavioural Therapies Centre, specializing in emotion regulation and stabilization. Results showed that staff reported a significant increase in mindfulness which had a positive impact upon their wellbeing and perceived ability to respond skilfully to challenging situations at work and at home. Gains were mostly in the first half of training but were maintained to the end and to follow-up. This adapted mindfulness training course appeared to be effective in meeting the need for a group of clinical staff to develop mindfulness. The potential impact upon patient engagement has been identified but further research into this area is indicated.